The tragedy of the anti-commons: a wew problem. An application to the fisheries - Filipe, José António (2010)
The operation and management of common property resources ("the commons") have been exhaustively examined in economics and political science, both in formal analysis and in practical applications. "Tragedy of the Commons" metaphor helps to explain why people overuse shared resources. On the other side, Anti-Commons Theory is a recent theory presented by scientists to explain several situations about new Property Rights concerns. An "anti-commons" problem arises when there are multiple rights to exclude. Little attention has been given to the setting where more than one person is assigned with exclusion rights, which may be exercised. We analyze the "anti-commons" problem in which resources are inefficiently under¬utilized rather than over-utilized as in the familiar commons setting. In fact, these two problems are symmetrical in several aspects.